Formulation development and production technology for a drink based on curd whey with the addition of fruit and vegetable raw materials - E. S. Smirnova; E. O. Melnikova; E. V. Razhina; N. L. Lopaeva; O. V. Chepushtanova (Новые технологии, 2025)
Introduction. According to the Doctrine of Industrial Safety, research in terms of the development and production of functional products is relevant. The main goal of functional products is to provide the body with the necessary components and protect it from negative factors. Milk whey is a secondary processing product, a source of biologically active substances, complete proteins and minerals. A recipe and production technology for a drink based on curd whey with the addition of fruit and vegetable raw materials have been developed. The results of quality assessment based on organoleptic and physicochemical indicators have been presented.The goal of the research is to develop a recipe and production technology for a fermented milk drink based on curd whey with the addition of fruit and vegetable raw materials.The methods. The quality of whey and finished samples was assessed by organoleptic and physicochemical indicators in accordance with GOST 34352-2017, GOST 33957-2016. Acidity was determined by the titrimetric method using the phenolphthalein indicator. The organoleptic properties of the whey and finished samples were assessed by tasting using the descriptive and analytical method. The tasting was carried out by an expert committee using a 5-point assessment scale.The results. Sample No. 2 (prunes and dried apricots) has been recognized as the best. It has a thick consistency with inclusions of the added additive evenly distributed throughout the mass; a sweet and sour taste and smell, with a fruity aftertaste characteristic of the added additives; and a dark creamy, uniform color. When analyzing the physicochemical parameters, the titratable acidity (°T) and oxidation-reduction potential parameters have been determined. It has been revealed that sample No. 2 has the highest values of the studied parameters (40°T and 352.5 mV, respectively).The conclusion. Based on the obtained data, we recommend the production of a fermented milk drink with the addition of prunes and dried apricots as enriching components.